1998
DOI: 10.1007/s002689900348
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Radiologic Treatment of Primary Budd‐Chiari Syndrome

Abstract: Budd-Chiari syndrome (BCS) is an uncommon form of portal hypertension caused by obstruction of the hepatic venous outflow. From 1969 to 1997 we treated 19 patients (7 men, 12 women; mean age 37.6 years) affected by primary BCS. In most of the cases no etiologic factors were identified; in the remaining cases the etiology was associated with polycythemia vera, use of oral contraceptives, presence of endoluminal membranes, and repeated episodes of sepsis. Three patients with membranous occlusion of the major hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Radiological interventions for both IVC and HV achieved technical success rates of more than 90% and long-term patency rates of more than 80%; also radiological re-interventions are usually successful [1,69,[77][78][79][80] . In our series, radiological intervention protocols according to morphology of the obstruction yielded good results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological interventions for both IVC and HV achieved technical success rates of more than 90% and long-term patency rates of more than 80%; also radiological re-interventions are usually successful [1,69,[77][78][79][80] . In our series, radiological intervention protocols according to morphology of the obstruction yielded good results.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty with TIPS may be associated splanchnic venous thrombosis, which can be successfully tackled by radiological interventions in the same session [89] . Technical success for TIPS ranges from 75% to 100% in various works [ of TIPS dysfunction (present in 40% to 75% if followed up for more than two years [80,82,84,90,91,93] ) necessitates reinter vention in up to 70% of cases [1,[87][88][89]91] , giving a revision rate of 1.4 revisions per patient [91] . TIPS related complications occur in less than 20% of patients [91] .…”
Section: Discussionmentioning
confidence: 99%
“…Although short-term results are excellent, the sustained patency rate is only 50% at two years after the procedure [143] . However, the use of intraluminal stents has been shown to increase the long-term patency rates to nearly 90% [144][145][146] . Once inserted, the stents cannot be removed, and placement of a stent above the intrahepatic IVC may interfere with liver transplantation.…”
Section: Managementmentioning
confidence: 99%
“…The concomitant use of stents has provided for extended patency rates, sometimes as high as 80% to 90%. 8,58,[60][61][62] In a recent series of cases of BCS associated with IVC obstruction, the investigators performed percutaneous balloon angioplasty of the vena cava in 42 patients. Membranous occlusion of the IVC was noted in 29 of these patients, whereas segmental obstruction was seen in the remaining 13 patients.…”
mentioning
confidence: 99%
“…Surgical shunt revision, angioplasty, and stenting are available alternatives to maintain long-term patency. 1,8,35,40,44,52,55,62,75,[77][78][79][80][81][82] A recent series showed that a side-to-side portocaval shunt, when placed early in cases of hepatic vein occlusion alone causing BCS, led to reversal of liver damage, prolonged survival, correction of hemodynamic abnormalities, and good quality of life. 83 Although highly effective, in our opinion, this type of shunting can impose technical difficulties in cases that eventually require liver transplantation.…”
mentioning
confidence: 99%